Influecne of Climate Warming on Arctic Mammals ? New Insights from Ancient DNA Studies of the collared lemming Dicrostonyx torquatus. - Stefan Prost (Max-Planck-Institut für evolutionäre Anthropologie); Nickolay Smirnov (Institute of Plant and Animal Ecology); Vadim B. Fedorov (Institute of Arctic Biology); Roberst S. Sommer (Ecology Centre); Mathias Stiller (Max-Planck-Institut für evolutionäre Anthropologie); Doris Nagel (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Michael Knapp (Max-Planck-Institut für evolutionäre Anthropologie) (PLoS ONE, 2010)
The abstract is available here: https://uscholar.univie.ac.at/o:244926 The abstract is available here: https://uscholar.univie.ac.at/o:244926